Forms and Practices of Interbudgetary Relations in USSR in 1950s — First Half of 1960s - S. A. Bakanov; I. A. Medvedev; N. Yu. Pivovarov (Научный диалог, 2022)
The forms and practices of interbudgetary relations in the USSR in the 1950s and early 1960s are considered. It is noted that the term interbudgetary relations in its broad interpretation can be used to describe the processes that took place in the budgetary system of the USSR. But, with one amendment: interbudgetary relations in the period under review should be understood as relations between the levels of the unified budgetary system of the Soviet Union, and not relations between equal subjects, as is interpreted in modern scientific literature. Record keeping materials of organizations, institutions and departments involved at different levels in the regulation of interbudgetary relations were used as sources. It is shown that interbudgetary relations took place in several forms: 1) the formation of th regulatory part of the revenues of lower budgets from tax deductions and revenues received by higher budgets; 2) implementation of interbudgetary transfers in the form of grants, subsidies and subventions; 3) implementation of the mechanism for settling budget disagreements. The authors come to the conclusion that each of these forms contributed to the achievement of a balance between the incomes of individual levels of the budget system and the expenditure obligations assigned to them.